2013
DOI: 10.1002/zaac.201300329
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step Synthesis of MoS2 Nanotubes using Shock Waves with Lead as Growth Promoter

Abstract: A new two‐step procedure for the synthesis of MoS2 nanotubes using lead as a growth promoter is reported. In the first step, molybdenum suboxide nanowhiskers containing a small amount of lead atoms were created by exposing a pressed MoS2+Pb mixture to highly compressed shock‐heated argon gas, with estimated temperatures exceeding 9900 K. In the second step, these molybdenum suboxide nanowhiskers served as templates for the sulfidization of the oxide into MoS2 nanotubes (by using H2S gas in a reducing atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…11,12 In recent years, a number of experimental methods on static and dynamic shock compression have been developed that lead to the synthesis of several multifunctional materials with outstanding properties compared to experimental methods performed at room temperature. 4,13 Carbon nanotubes (CNTs) have played the pivotal role in nanoscience and technology due to their outstanding performances as well as ever-increasing applications in versatile fields. In that way, there has been significant research effort to synthesize multifunctional crystalline CNTs and diamond materials by static and dynamic pressure compression methods because crystalline materials have numerous advantages for commercial applications compared to amorphous materials, due to their outstanding physical, chemical, and mechanical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,12 In recent years, a number of experimental methods on static and dynamic shock compression have been developed that lead to the synthesis of several multifunctional materials with outstanding properties compared to experimental methods performed at room temperature. 4,13 Carbon nanotubes (CNTs) have played the pivotal role in nanoscience and technology due to their outstanding performances as well as ever-increasing applications in versatile fields. In that way, there has been significant research effort to synthesize multifunctional crystalline CNTs and diamond materials by static and dynamic pressure compression methods because crystalline materials have numerous advantages for commercial applications compared to amorphous materials, due to their outstanding physical, chemical, and mechanical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To show the significance of shock recovery experiments, few examples of recent reports are listed below. Brontvein et al [9] utilized shock waves as a growth promoter to synthesize two-step MoS 2 nano-tubes with argon as driver gas and phase transformation was demonstrated in fluorite CeO 5 CrO·5O 2+x under shock wave-loaded conditions [10]. Cubic zirconia showed unstable electronic structure and crystalline structure and CeO 2 showed the stable physical properties in shock wave-loaded conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many synthetic methods have been explored to fabricate MoS 2 nanotubes, for example, solvothermal, 9 hydrothermal, 10 high-temperature synthesis, 11 and thermal evaporation methods. 12 Numerous studies have shown that MoS 2 nanotubes have super properties in the application of nanoscale sensors, 13 optoelectronics, 14 electrochemistry, 15 catalysts, 16 and lubrication.…”
Section: Introductionmentioning
confidence: 99%